Estudo de espalhamento Raman em cristais de L-tirosina hidroclorídrica submetidos a altas pressões - SANTOS, Carlos Alberto Andrade Serra dos (2017)
In this work L-tyrosine hydrochloride crystals (LTHCl) were prepared by slow evaporation technique at room temperature and characterization by X-ray diffraction, thermogravimetry, differential thermal analysis, differential scanning calorimetry and Raman scattering at room temperature and under high pressures. After four weeks, it was possible obtain various crystals of good crystalline quality. The solution was acidic with pH 1.2. From the XRD pattern of the material and the Rietveld analysis, it was found that at room temperature LTHCl crystallizes in monoclinic space group (P21) with two molecules per unit cell. The refinement quality parameters were satisfactory with Rp = 6.29 %, Rwp = 8.49 % and S = 1.34. The thermal analysis showed that the material undergoes fusion around 231°C and presented no thermal event that features phase transition before the fusion. Furthermore, thermal analysis showed that the crystal is stable up to 220°C. Calculations using DFT (Functional Density Theory) were performed to identify the vibrational modes in the LTHCl crystal. Raman scattering measurements as a function of pressure (0,0-7,2 GPa) showed as major changes: the occurrence of an inversion of intensity between a strong band (attributed to torsion of L-tyrosine molecule) and an imperceptible band (at ambient pressure) for pressures above 2,5 GPa and a discontinuity of dω/dP associated with the strong band between 1.0 and 1.5 GPa, suggesting a conformational transition above 1.5 GPa stabilizing the structure up to 7,2 GPa. In the region of the internal modes few changes were observed, with the downshift of the COOH and NH3+ units as one of them. Finally, the decompression reinforced that the conformational phase transition is reversible, demonstrating a great capacity of this material to regenerate its original structure without presenting hysteresis.